Room-temperature upcycling of agricultural waste to carbon dots and its application as a selective fluorescence nanoprobe for iron (III) analysis in diverse samples - Heba M. Hashem; Mahmoud El-Maghrabey; Hadir Borg; Galal Magdy; Fathalla Belal; Rania El-Shaheny (Talanta Open)
A smart, green, practical, and scalable method has been developed for the upcycling of orange peels into carbon dots (C-dots) by room-temperature alkali treatment for the first time. The prepared C-dots showed excellent fluorescence emission at 428 nm upon excitation at 333 nm. As well, the C-dots exhibit high water stability and aqueous solubility, and a tiny particle size of 1.74 ± 0.44 nm. Based on the selective quenching of the synthesized C-dots fluorescence by Fe3+, a new fast and green fluorescence probe has been validated for the determination of Fe3+over the concentration range of 1.0–400.0 µM with a detection limit of 0.2 µM (11.2 ppb). The selectivity of the sensor has been established over various metal ions and insecticides. The developed sensor has been utilized for the determination of Fe3+ in different environmental water samples, such as river, irrigation, and tap water, with an excellent recovery % (99.08–108.24 %). Besides, the new probe has been applied for Fe3+ determination in ampoules with an average recovery % of 99.86±1.15. The environmental impact of the new method has been positively confirmed by ComplexGAPI and AGREE metrics. Furthermore, the method's blueness has been estimated by the blue applicability grade index (BAGI), and the obtained high score (70) demonstrates the high practicability of the method. The method whiteness has also been assessed by the RGB 12 algorithm, which gives a whiteness parameter of 92.5 that highlights its practicality, greenness, and analytical performance. Besides, the presented approach is the first to valorize agricultural waste by room-temperature treatment, a merit that opens the door for broad applications in limited-income laboratories.